Advertising campaign of gum littering problem among Malaysians in urban cities / Nuranis Mohd Nor Jamalul Lail - Mohd Nor Jamalul Lail, Nuranis (2013)
Malaysian is known by their habit of littering. Everywhere around Malaysia cities, there can be spotted little rubbish here and there such as cigarettes buds, chewing gum, plastic bag, tissue or bottles lying on the street ground. This is a big issue in Malaysia because our government does not tackle this issue aggressively. Malaysia don’t fine those who litter and day by day Malaysians are becoming careless, irresponsible and lazy to throw rubbish in the bin because it’s simply easier to throw it on the streets